Time course of serum cobalamin, folate, and total iron binding capacity concentrations in pregnant bitches and association with hematological variables and survival. (30th June 2019) - Nivy, Ran; Mazaki‐Tovi, Michal; Aroch, Itamar; Tal, Smadar
Abstract: Background: Hypocobalaminemia, hypofolatemia and iron deficiency are associated with pregnancy‐related anemia (PRA) and neonatal survival (NS) in women. Similar associations have not been investigated in pregnant bitches. Objectives: To investigate time course and associations of serum cobalamin, folate and iron status indicators with hematological variables and NS in pregnant bitches. Animals: Forty‐eight pregnant bitches. Methods: A prospective cohort study. Pregnancy was confirmed by abdominal ultrasonography twice during mid‐ and late pregnancy, concurrently with blood sampling. Associations among pregnancy stage, NS and laboratory variables were assessed by generalized estimating equations. Results: Compared with midpregnancy, serum cobalamin (adjusted mean [95% confidence interval, CI]) decreased at late pregnancy (430 pg/mL [394‐466] versus 330 pg/mL [303‐357], respectively; P  < .001), whereas serum folate did not. Every increment of 1 in parity number or litter size corresponded to 28.6 pg/mL (95% CI, 5.6‐51.6; P = .02) and 20.3 pg/mL (95% CI, 10.9‐29.7; P  < .001) decrease in serum cobalamin concentration. Compared with midpregnancy, serum iron ( P  < .001) and transferrin saturation ( P = .01) increased at late pregnancy. The decrease in red blood cell count ( P  < .001) at late pregnancy was significantly, albeit weakly, correlated with decreasing serum folate concentration ( r = 0.33; P = .02). None of the measures was associated with NS. Conclusions and Clinical Significance: Pregnancy‐related anemia was common at late pregnancy. Unlike in women, in pregnant bitches, serum iron and transferrin saturation were increased at late pregnancy. Future studies are warranted to investigate the clinical ramifications of hypocobalaminemia in pregnant bitches and the utility of prophylactic folate administration in mitigating PRA.